Examples of homogeneous vectors on the Fiber space of the associated and the tangent bundles - R. Chavosh Khatamy (Հայաստանի ԳԱԱ)
We give special examples of odd dimensional solvable Lie groups equipped with left invariant Riemannian metric, and we prove some conditions about the existence of homogeneous (geodesic) vectors on the fiber space of ξ and τG/K.
Keywords: Mathematics; Science